Badania Kliniczne i Doświadczalne w Chorobach Serca, Płuc i Naczyń Immunosuppression protocols in lung transplantation taking into account own experience - Wojarski, Jacek; Kucewicz-Czech, Ewa; Przybylski, Roman; Jastrzębski, Dariusz; Zakliczyński, Michał; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Acute cellular rejection in lung transplantation (LTx) is extremely strong. Long-term results of LTx are limited by bronchiolitis obliterans, which is a process associated by many authors with „chronic rejection” [1]. This may lead to the conclusion that improvement of immunosuppression will limit the occurrence and severity of OB. The optimal immunosuppressive regimen still remains to be established – especially when new drugs become available. The authors describe immunosuppressive drugs that may be currently used for LTx patients. Medical aspects directing decisions about a model of immunosuppression are also described. Own clinical experience with a novel immunosuppressive regimen is discussed.